Cardiac Protection by Oral Sodium Thiosulfate in a Rat Model of L-NNA-Induced Heart Disease - Nguyen, Isabel T. N.; Wiggenhauser, Lucas M.; Bulthuis, Marian; Hillebrands, Jan-Luuk; Feelisch, Martin; Verhaar, Marianne C.; van Goor, Harry; Joles, Jaap A. (Frontiers in Pharmacology, 2021)
Hypertension contributes to cardiac damage and remodeling. Despite the availability of renin-angiotensin system inhibitors and other antihypertensive therapies, some patients still develop heart failure. Novel therapeutic approaches are required that are effective and without major adverse effects. Sodium Thiosulfate (STS), a reversible oxidation product of hydrogen sulfide (H2S), is a promising pharmacological entity with vasodilator and anti-oxidant potential that is clinically approved for the treatment of calciphylaxis and cyanide poisoning. We hypothesized that Sodium Thiosulfate improves cardiac disease in an experimental hypertension model and sought to investigate its cardioprotective effects by direct comparison to the ACE-inhibitor lisinopril, alone and in combination, using a rat model of chronic nitric oxide (NO) deficiency. Systemic nitric oxide production was inhibited in Sprague Dawley rats by administering N-ω-nitro-l-arginine (L-NNA) with the food for three weeks, leading to progressive hypertension, cardiac dysfunction and remodeling. We observed that STS, orally administered via the drinking water, ameliorated L-NNA-induced heart disease. Treatment with STS for two weeks ameliorated hypertension and improved systolic function, left ventricular hypertrophy, cardiac fibrosis and oxidative stress, without causing metabolic acidosis as is sometimes observed following parenteral administration of this drug. STS and lisinopril had similar protective effects that were not additive when combined. Our findings indicate that oral intervention with a H2S donor such as STS has cardioprotective properties without noticeable side effects.